Mutation and polymorphism spectrum in osteogenesis imperfecta type II: implications for genotype–phenotype relationships - Bodian, Dale L. (Oxford University Press, 2009)
Osteogenesis imperfecta (OI), also known as brittle bone disease, is a clinically and genetically heterogeneous disorder primarily characterized by susceptibility to fracture. Although OI generally results from mutations in the type I collagen genes, COL1A1 and COL1A2, the relationship between genotype and phenotype is not yet well understood. To provide additional data for genotype–phenotype analyses and to determine the proportion of mutations in the type I collagen genes among subjects with lethal forms of OI, we sequenced the coding and exon-flanking regions of COL1A1 and COL1A2 in a cohort of 63 subjects with OI type II, the perinatal lethal form of the disease. We identified 61 distinct heterozygous mutations in type I collagen, including five non-synonymous rare variants of unknown significance, of which 43 had not been seen previously. In addition, we found 60 SNPs in COL1A1, of which 17 were not reported previously, and 82 in COL1A2, of which 18 are novel. In three samples without collagen mutations, we found inactivating mutations in CRTAP and LEPRE1, suggesting a frequency of these recessive mutations of ∼5% in OI type II. A computational model that predicts the outcome of substitutions for glycine within the triple helical domain of collagen α1(I) chains predicted lethality with ∼90% accuracy. The results contribute to the understanding of the etiology of OI by providing data to evaluate and refine current models relating genotype to phenotype and by providing an unbiased indication of the relative frequency of mutations in OI-associated genes.